2019
DOI: 10.1111/inm.12575
|View full text |Cite
|
Sign up to set email alerts
|

What nonpharmacological therapeutic interventions are provided to adolescents admitted to general mental health inpatient units? A descriptive review

Abstract: Limited research exists regarding the therapeutic operations of adolescent mental health inpatient units, particularly in terms of nonpharmacological therapeutic interventions. This review collates what is known about reported nonpharmacological therapeutic interventions for young people admitted to general or non‐disorder‐specific adolescent mental health inpatient settings. A descriptive review of this nature was not located in the literature. The aim was to identify what is currently known about reported no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…2007; Hayes et al . 2019b; Rasmussen et al . 2017) and how ward management fails to relate nursing ideology to nursing models, theories, and ethics (Ellilä et al .…”
Section: Discussionmentioning
confidence: 99%
“…2007; Hayes et al . 2019b; Rasmussen et al . 2017) and how ward management fails to relate nursing ideology to nursing models, theories, and ethics (Ellilä et al .…”
Section: Discussionmentioning
confidence: 99%
“…We add to the growing evidence that physical health monitoring in mental healthcare is necessary, particularly for adolescents. [11][12][13][30][31][32] Previous research also shows that metabolic abnormalities are common in adolescents receiving mental healthcare, but often go unnoticed and untreated. 6,10,13,21 Individuals admitted to generic and secure mental health wards have a wide range of difficulties and non-specific mental health needs, and may or may not be prescribed psychotropic medication.…”
Section: Importance Of Monitoringmentioning
confidence: 99%
“…Hayes et al reviewed non-pharmacological interventions delivered on in-patient wards and found psychosocial programmes, such as therapy-based activities, family interventions and mindfulness-based activities, were common. 32 Yet, few studies have been conducted offering physical health interventions within this setting, or even those across the general population, despite the benefits of exercise for adolescents. 33 Further, a recent review showed that despite being recommended by NICE, lifestyle interventions are not consistently offered across mental health trusts in the UK.…”
Section: Recommendations and Future Workmentioning
confidence: 99%
“…Interviewees described both positive and negative impressions of the effectiveness of psychiatric hospitalization for adolescents experiencing a suicide-related crisis. Although the effectiveness of psychiatric hospitalization is highly debated [ 48 ], discharge summaries including an overview of the purpose of hospitalization (i.e., stabilization and safety) and the expectation that recovery is a longer-term process involving ongoing outpatient care following discharge [ 49 ], may help school professionals better understand adolescents’ treatment. Such information may also reinforce the importance of school supports during reintegration.…”
Section: Discussionmentioning
confidence: 99%